2016
DOI: 10.1038/srep37064
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate lyase ablation disrupts presynaptic architecture and function via an ubiquitin- proteasome mediated mechanism

Abstract: The bioactive lipid sphingosine 1-phosphate (S1P) is a degradation product of sphingolipids that are particularly abundant in neurons. We have shown previously that neuronal S1P accumulation is toxic leading to ER-stress and an increase in intracellular calcium. To clarify the neuronal function of S1P, we generated brain-specific knockout mouse models in which S1P-lyase (SPL), the enzyme responsible for irreversible S1P cleavage was inactivated. Constitutive ablation of SPL in the brain (SPLfl/fl/Nes) but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 54 publications
3
52
0
Order By: Relevance
“…We have shown earlier that neural‐targeted depletion of SGPL1 causes accumulation of S1P and to a lesser extent of sphingosine in brains, whereas the levels of other sphingolipids including ceramide and sphingomyelin are not affected (Mitroi et al, ). We now assessed the levels of sphingolipids and the expression of SGPL1 in primary cultured microglial cells and astrocytes generated from these mice.…”
Section: Resultsmentioning
confidence: 97%
“…We have shown earlier that neural‐targeted depletion of SGPL1 causes accumulation of S1P and to a lesser extent of sphingosine in brains, whereas the levels of other sphingolipids including ceramide and sphingomyelin are not affected (Mitroi et al, ). We now assessed the levels of sphingolipids and the expression of SGPL1 in primary cultured microglial cells and astrocytes generated from these mice.…”
Section: Resultsmentioning
confidence: 97%
“…Notably, inhibition of SPHKs neither rescued LC3-I conversion into LC3-II nor reduced APP accumulation. Another possibility that cannot be fully excluded is the role of sphingosine in autophagy, which is also accumulating to a certain extent in SGPL1-deficient neurons 15,26 . Sphingosine has recently been demonstrated to trigger calcium release from acidic stores, 34 that in turn might activate autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed mechanism involved in the regulation of autophagy by PE linked via SGPL1 to S1P metabolism is yet to be explored. We recently generated a new mouse model (SGPL1 fl/fl/Nes ) with developmental neural specific ablation of SGPL1 in the brain, which causes a considerable accumulation of S1P and its metabolic precursor sphingosine with no changes in ceramide and sphingomyelin in the brain 15 . Here we report that neural-targeted depletion of SGPL1 causes cognitive deficits and a decrease of brain PE content along with impaired autophagy and a consequent accumulation of neurodegenerative biomarkers in the brains of SGPL1 fl/fl/Nes mice.…”
Section: Introductionmentioning
confidence: 99%
“…; Mitroi et al . ), which is mediated by exocytosis of neurotransmitter‐containing synaptic vesicles (Sudhof and Rizo ). Consequently, it has been suggested that S1P may regulate the release of neurotransmitters or hormones from hippocampal neurons (Kajimoto et al .…”
mentioning
confidence: 99%
“…Sphingosine-1-phosphate (S1P), an essential bioactive sphingolipid concentrated in the brain and involved in many neurological diseases (Edsall and Spiegel 1999;Takabe et al 2008), plays many physiological roles in neurons, such as neuronal development (Mizugishi et al 2005), neurite extension and retraction (Toman et al 2004;Strochlic et al 2008), and neuronal excitability (MacLennan et al 2001;Zhang et al 2006). Notably, S1P may modulate the strength of synaptic transmission (Kanno et al 2010;Mitroi et al 2016), which is mediated by exocytosis of neurotransmittercontaining synaptic vesicles (Sudhof and Rizo 2011). Consequently, it has been suggested that S1P may regulate the release of neurotransmitters or hormones from hippocampal neurons (Kajimoto et al 2007;Riganti et al 2016;Darios et al 2017), zona glomerulosa cells , neuromuscular junctions (Brailoiu et al 2002) and neuroendocrine chromaffin cells (Pan et al 2006;Darios et al 2017).…”
mentioning
confidence: 99%